2010
DOI: 10.1029/2010gl044347
|View full text |Cite
|
Sign up to set email alerts
|

Large fault fabric of the Ninetyeast Ridge implies near‐spreading ridge formation

Abstract: [1] Ninetyeast Ridge (NER) is a linear volcanic ridge in the Indian Ocean thought to have formed by hotspot volcanism on the northward-drifting Indian plate. Geological data from the ridge are sparse, so its tectonic evolution is poorly known. We studied satellite-derived gravity data, seismic reflection profiles, and multibeam bathymetry to examine NER structure. Gravity data show that the ridge displays a series of nearly E-W trending lineations with average spacing ∼0.4°(45 km). In seismic and bathymetry da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 23 publications
(35 reference statements)
1
27
0
3
Order By: Relevance
“…Earlier derived crustal models show the presence of thicker crust with and without underplating below these ridges (Detrick and Watts, 1979;Mukhopadhyay and Krishna, 1995;Subrahmanyam et al, 1999;Grevemeyer et al, 2001;Krishna et al, 2001b;Krishna, 2003;Subrahmanyam et al, 2008;Radhakrishna et al, 2010). The present analysis revealed that both ridges, in general, are earlier investigators for the ridge south of 2ºN revealed that this part of the ridge had evolved due to frequent ridge jumps in the vicinity of the Kerguelen hot spot during the rapid northward migration of the Wharton spreading ridge (Royer et al, 1991;Krishna et al, 1999;Sager et al, 2010;Krishna et al, 2012). The modeled lithosphere structure across these ridges suggests a lack of plume impact at the LAB, although there is minor eastward thinning beneath the Ninetyeast Ridge.…”
Section: Geodynamic Implicationssupporting
confidence: 64%
“…Earlier derived crustal models show the presence of thicker crust with and without underplating below these ridges (Detrick and Watts, 1979;Mukhopadhyay and Krishna, 1995;Subrahmanyam et al, 1999;Grevemeyer et al, 2001;Krishna et al, 2001b;Krishna, 2003;Subrahmanyam et al, 2008;Radhakrishna et al, 2010). The present analysis revealed that both ridges, in general, are earlier investigators for the ridge south of 2ºN revealed that this part of the ridge had evolved due to frequent ridge jumps in the vicinity of the Kerguelen hot spot during the rapid northward migration of the Wharton spreading ridge (Royer et al, 1991;Krishna et al, 1999;Sager et al, 2010;Krishna et al, 2012). The modeled lithosphere structure across these ridges suggests a lack of plume impact at the LAB, although there is minor eastward thinning beneath the Ninetyeast Ridge.…”
Section: Geodynamic Implicationssupporting
confidence: 64%
“…E‐W bathymetric lineations also occur at this site; however, they are not as distinct as at Sites 216 and 758. The most prominent lineation is the trough at the south flank of the seamount, which is a large graben that was probably formed during the construction of the NER [ Sager et al ., ]. Other lineations have similar trends crossing the top of the seamount, with several being traced across the entire summit (Figure ).…”
Section: Ner Fault Observationsmentioning
confidence: 99%
“…Many different authors have explained the formation of the NER as a result of various tectonic anomalies [see review by Royer et al ., ], but the modern consensus is that it was created by hot spot volcanism that emplaced a ridge on the northward drifting Indian plate from Late Cretaceous to early Cenozoic time [ Royer et al ., ; Krishna et al ., ]. The hot spot was often located near the spreading ridge [ Sager et al ., ; Krishna et al ., ] and changes in NER morphology may be related to the proximity of the hot spot to the spreading ridge [ Royer et al ., ]. Because of its near‐ridge location, the hot spot emplaced material on both the Indian and Antarctic plates, with most of the volcanic product ending up on the India plate owing to repeated southward ridge jumps [ Krishna et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The seafloor morphology of the NER all along its length (Figures and ) is quite variable. As noticed previously [ Sclater and Fisher , ; Krishna et al ., , ; Sager et al ., , ], south of 10°S, the ridge feature is prominent and continuous with an average width and relief of 200 and 3 km, respectively. The NER segment between 10°S and equator has distinct morphology of isolated rises with a narrow width of ~100 km.…”
Section: Analyses Of Bathymetry Gravity Geoid and Sediment Thicknementioning
confidence: 99%